Dysfunction of the Hippocampal-Lateral Septal Circuit Impairs Risk Assessment in Epileptic Mice - Cao, Yi; Sun, Chongyang; Huang, Jianyu; Sun, Peng; Wang, Lulu; He, Shuyu; Liao, Jianxiang; Lu, Zhonghua; Lu, Yi; Zhong, Cheng (Frontiers in Molecular Neuroscience, 2022)
Temporal lobe epilepsy, a chronic disease of the brain characterized by degeneration of the hippocampus, has impaired risk assessment. Risk assessment is vital for survival in complex environments with potential threats. However, the underlying mechanisms remain largely unknown. The intricate balance of gene regulation and expression across different brain regions is related to the structure and function of specific neuron subtypes. In particular, excitation/inhibition imbalance caused by hyperexcitability of glutamatergic neurons and/or dysfunction of GABAergic neurons, have been implicated in epilepsy. First, we estimated the risk assessment (RA) by evaluating the behavior of mice in the center of the elevated plus maze, and found that the kainic acid-induced temporal lobe epilepsy mice were specifically impaired their RA. This experiment evaluated approach-RA, with a forthcoming approach to the open arm, and avoid-RA, with forthcoming avoidance of the open arm. Next, results from free-moving electrophysiological recordings showed that in the hippocampus, ~7% of putative glutamatergic neurons and ~15% of putative GABAergic neurons were preferentially responsive to either approach-risk assessment or avoid-risk assessment, respectively. In addition, ~12% and ~8% of dorsal lateral septum GABAergic neurons were preferentially responsive to approach-risk assessment and avoid-risk assessment, respectively. Notably, during the impaired approach-risk assessment, the favorably activated dorsal dentate gyrus and CA3 glutamatergic neurons increased (~9%) and dorsal dentate gyrus and CA3 GABAergic neurons decreased (~7%) in the temporal lobe epilepsy mice. Then, we used RNA sequencing and immunohistochemical staining to investigate which subtype of GABAergic neuron loss may contribute to excitation/inhibition imbalance. The results show that temporal lobe epilepsy mice exhibit significant neuronal loss and reorganization of neural networks. In particular, the dorsal dentate gyrus and CA3 somatostatin-positive neurons and dorsal lateral septum cholecystokinin-positive neurons are selectively vulnerable to damage after temporal lobe epilepsy. Manipulation of the hippocampal glutamatergic or somatostatin neurons directly disrupts RA, suggesting that an excitation/inhibition imbalance in the dorsal hippocampus results in the impairment of RA behavior. Taken together, this study provides insight into epilepsy and its comorbidity at different levels, including molecular, cell, neural circuit, and behavior, which are expected to decrease injury and premature mortality in patients with epilepsy.